How do you know [videorecording (DVD)] - Brooks, James L.; Brooks, James L.; Brooks, James L.; Witherspoon, Reese, 1976-; Wilson, Owen, 1968-; Rudd, Paul; Nicholson, Jack; Hahn, Kathryn, 1974-; Linn-Baker, Mark; McLarty, Ron (Sony Pictures Home Entertainment, 2011)
A professional softball player discovers she is in the middle of a love triangle after she falls for two different men and wonders when it comes to love, how do you know?